Open : how we'll work, live and learn in the future - Price, David, ....- (S.l. : Crux, 2013)
"What makes a global corporation give away its prized intellectual property? Why are Ivy League universities allowing anyone to take their courses for free? What drives a farmer in rural Africa to share his secrets with his competitors? A collection of hactivists, hobbyists, forum-users and maverick leaders are leading a quiet but unstoppable revolution. They are sharing everything they know, and turning knowledge into action in ways that were unimaginable even a decade ago. Driven by technology, and shaped by common values, going ‘open' has transformed the way we live. It's not so much a question of if our workplaces, schools and colleges go open, but when. Packed with illustration and advice, this entertaining read by learning futurist, David Price, argues that ‘open' is not only affecting how we are choosing to live, but that it's going to be the difference between success and failure in the future."
Keywords: Information technology Economic aspects; Economic development Technological innovations